ANALISIS KEBERADAAN CELE DALAM PERSEFEKTIF KEBHINEKAAN GLOBAL - Sitti Rochmi Tatisina; Lisye Salamor; Jumiati Tuharea (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Indonesia's cultural diversity can be said to have advantages compared to other countries. This illustrates that basically it is not easy to unite diversity without a national character that has noble character and is guided by the principles of Pancasila. This research aims to determine the understanding of students, teachers and the opinions of the Education Department regarding the wearing of cele clothes in educational institutions. This author entitled